Contagion : Monsoonal Effects, Spillovers, and Jumps Between Multiple Equilibria - Masson, Paul (IMF Working Papers; Working Paper, 1998)
Several concepts of contagion are distinguished. It is argued that only models that admit of multiple equilibria are capable of producing true contagion. A simple balance of payments model is presented to illustrate that phenomenon, and some back-of-the-envelope calculations assess its relevance to the coincidence of emerging market crises in 1994-95 and in 1997.